A decade of Benzodiazepine and Z-drug use in Hong Kong: a longitudinal studyResearch in context - Kyung Jin Lee; Yue Wei; Shek-Ming Leung; Caige Huang; Hei Hang Edmund Yiu; Eunice Kehui Deng; David J. Castle; Simon S.Y. Lui; Vincent K.C. Wong; Ian C.K. Wong; Esther W. Chan (The Lancet Regional Health. Western Pacific)
Summary: Background: Concerns are growing about the long-term use of benzodiazepines (BZDs) and non-benzodiazepines (Z-drugs) due to adverse effects such as drug tolerance, dependence, cognitive dysfunction, and falls, particularly in the elderly. This study aims to understand thorough prescribing patterns of BZDs and Z-drugs across age groups in clinical settings of Hong Kong, especially the long-term prescriptions. Methods: Using territory-wide electronic health record data from Hong Kong (2014–2023), we analysed the prevalence, incidence, and duration of BZD and Z-drug prescriptions in adults. Long-term use was defined as prescriptions exceeding 90 days. Joinpoint regression models assessed trend changes, focusing on four age groups: 18–25, 26–49, 50–64, and ≥65. Psychiatric diagnoses within 180 days before and after treatment initiation were also evaluated. Findings: Patients with BZD and Z-drug prescribing increased from 2014 to 2023, with an average annual percentage change (AAPC) of 3.44 [95% CI: 3.26–3.61] in prevalence and 1.51 [0.64–2.45] in incidence. Trends varied by age: the sharpest increases were observed in young adults aged 18–25 (prevalence AAPC: 9.43 [8.36–10.51]; incidence AAPC: 7.56 [6.19–8.89]), whereas the incidence in those aged ≥65 declined after 2019, although it remained the highest. Prevalence of patients with long-term prescribing rose consistently, particularly in young adults (BZD AAPC: 13.43 [11.98–14.62]; Z-drug AAPC: 12.88 [7.85–18.24]). Depression and dementia were the most common psychiatric diagnoses within 180 days before and after treatment initiation. Interpretation: These findings highlight the need to review long-term prescribing practices and establish clear guidelines for safe BZD and Z-drug use, especially among young adults. Funding: No funding has been provided for this research.